Administrative-Law Status of National Security Agencies - Inna PIDBEREZNYKH; Ivanna HORBACH-KUDRIA; Sergii GOLUBYTSKYI; Anatoliy BABICHEV; Mykhailo LOSHYTSKYI (Revista Jurídica Portucalense)
The article analyses the administrative-law approaches that regulate the activities of national security agencies with an emphasis on their ability to adapt to new challenges. The aim is to critically evaluate legal standards and organizational structures that determine the functions and responsibilities of national security agencies, as well as their impact on the overall security system. The research employs the methods of legal analysis, comparative research and studies cases covering both regulatory and empirical approaches, as well as scenario modelling. The results of the study revealed significant differences in the legal framework of different countries and pointed to weak coordination between the main security services. Unlike the traditional approach, where administrative and legal aspects are considered separately, this study integrates these issues to better understand national security management. The conclusions emphasize the need to improve legal norms and strengthen interdepartmental cooperation in order to improve the effectiveness of security management. Prospects for further research include analysis of the impact of new technologies on administrative processes and legal regulations in the context of national security, with a special emphasis on increasing adaptability to modern threats.